POTENSI KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) SEBAGAI PEWARNA ALAMI DALAM PEMBUATAN ES KRIM - diba 'izzati, farah; Ismanto, Arif; Anggraini, Mita (Jurnal Teknologi Hasil Peternakan, 2025)
This study aimed to evaluate the potential use of reddragon fruit (Hylocereus polyrhizus) peel extract as a naturalcoloring agent in ice cream production. The experimentemployed a Completely Randomized Design (CRD) withfive extract concentration treatments: 0%, 3%, 6%, 9%, and12%, each replicated three times. The observed parametersincluded pH, color values (L*, a*, b*), and organolepticproperties covering color, aroma, taste, and texture.Statistical analysis was performed using ANOVA (Analysisof Variance) for physical data and the Kruskal–Wallis test fororganoleptic data. When significant differences amongtreatments were found, DMRT (Duncan Multiple RangeTest) was applied for further analysis. The results indicateda decrease in pH with increasing extract concentration (from6.92 in the control to 6.60 at 12%). The L* value (lightness)decreased, while the a* value (redness) significantlyincreased with higher extract levels. Organoleptic evaluationshowed increased preference for color but decreasedacceptance of aroma, taste, and texture at higherconcentrations, presumably due to tannin compounds thatproduced astringent taste and odor, influencing panelists’perception. Therefore, red dragon fruit peel extract haspotential as a natural pigment capable of producing anappealing red color in ice cream